Contextualizing the Hadith on the Prohibition of Drawing Living Things: An Analysis of Logo Visualization in Modern Periods: Kontekstualisasi Hadits Larangan Menggambar Makhluk Hidup: Analisis Visualisasi Logo di Zaman Modern - Rinanda Komara, Wildan; Hermawan, Acep; Kosim, Abdul (Institut Agama Islam Negeri Kerinci, 2023)
This article departs from the view of some logo designers in Indonesia who avoid using images of animate beings in their designs. So this article attempts to explore the hadith of the prohibition of drawing living things contextually. On the other hand, the development of image visualization has developed in various variants, one of which is the logo as an industrial tool in the present. This study uses the library research method, which collects data through literature study of books, notes, and reports relevant to the problem under study. The results show that there are three main reasons ('illat) that cause the prohibition of drawing animate beings: first, if it aims to match the creation of Allah SWT; second, because it resembles the actions of Ahlul Kitab; third, because the image can be a means towards shirk. Meanwhile, the purpose of creating a logo is for the identity of a business, company, or organization to make it easily recognizable, differentiate it from other entities, and as a communication tool of what it offers. Given that the reason for the prohibition of drawing animate beings is irrelevant to the function of the logo, the law of creating a logo with visualization of animate beings is permissible.